THE INFLUENCE OF SOCIAL MEDIA USAGE AND ELECTRONIC WORD OF MOUTH ON PURCHASE INTENTION MEDIATED BY BRAND EQUITY - Devanda Martianta Sabeliana; Jonet Ariyanto Nugroho (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study aims to examine the influence of social media usage and electronic word of mouth (eWOM) on purchase intention, with brand equity serving as a mediating variable among Generation Z fashion consumers in Surakarta City. A quantitative research design was employed, and data were collected through questionnaires distributed to 399 respondents selected using purposive sampling. The data were analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach. The findings indicate that both social media usage and eWOM have a positive and significant direct effect on purchase intention. Additionally, both variables indirectly influence purchase intention through brand equity. Brand equity itself plays a significant role in strengthening consumers’ intention to purchase. These results highlight the importance of building strong brand equity to maximize the effectiveness of social media marketing and electronic word of mouth strategies. However, this study is limited to Generation Z consumers in a single city, which may limit the generalizability of the findings. Future research is recommended to include broader demographic groups and wider geographic areas to enhance the robustness and applicability of the results. Keywords: Social Media Usage; Electronic Word of Mouth ; Brand Equity; Purchase Intention ; Generation Z ; Fashion